dpr and sod in Streptococcus mutans Are Involved in Coexistence with S. sanguinis, and PerR Is Associated with Resistance to H(2)O(2) - Fujishima, Kei (American Society for Microbiology, 2013)
Large numbers of bacteria coexist in the oral cavity. Streptococcus sanguinis, one of the major bacteria in dental plaque, produces hydrogen peroxide (H(2)O(2)), which interferes with the growth of other bacteria. Streptococcus mutans, a cariogenic bacterium, can coexist with S. sanguinis in dental plaque, but to do so, it needs a means of detoxifying the H(2)O(2) produced by S. sanguinis. In this study, we investigated the association of three oxidative stress factors, Dpr, superoxide dismutase (SOD), and AhpCF, with the resistance of S. sanguinis to H(2)O(2). The knockout of dpr and sod significantly increased susceptibility to H(2)O(2), while the knockout of ahpCF had no apparent effect on susceptibility. In particular, dpr inactivation resulted in hypersensitivity to H(2)O(2). Next, we sought to identify the factor(s) involved in the regulation of these oxidative stress genes and found that PerR negatively regulated dpr expression. The knockout of perR caused increased dpr expression levels, resulting in low-level susceptibility to H(2)O(2) compared with the wild type. Furthermore, we evaluated the roles of perR, dpr, and sod when S. mutans was cocultured with S. sanguinis. Culturing of the dpr or sod mutant with S. sanguinis showed a significant decrease in the S. mutans population ratio compared with the wild type, while the perR mutant increased the ratio. Our results suggest that dpr and sod in S. mutans are involved in coexistence with S. sanguinis, and PerR is associated with resistance to H(2)O(2) in regulating the expression of Dpr.